Legal Regulation Experience of Individual Countries of The European Region Regarding Implementation of International Standards for Ensuring Criminological and Criminal-Legal Protection of Justice - Yuliia Khrystova; Serhiy Miroshnychenko; Iryna Kurbatova; Oleksiy Titarenkо; Maksym Maksimentsev (Jurnal Cita Hukum, 2024)
The article describes experience of Germany and Austria in implementing international standards for ensuring criminological and criminal-legal protection of justice. A set of general scientific and specific scientific research methods were used in the preparation of this article in order to define special subjects authorized to carry out such criminological activities, peculiarities of their interaction with the police and other law enforcement agencies, to reveal the content of legislative mandates regarding organization and functioning of the Court Security Services and their counterparts, as well as that of the legislation on criminal liability for criminal offenses against justice. The purpose of this work is to determine promising directions for increasing efficiency of implementing criminological and criminal-legal protection of justice by authorized subjects in Ukraine, which has become especially important in the sphere of ensuring national security under martial law, taking into account positive experience of such European region countries as Germany and Austria regarding implementation of international standards recognized by the international community in this area. Based on the results of the research, prospective directions for improving the activity of the Court Security Service of Ukraine, its interaction with the National Police and other subjects of the state sector and non-state sector in provision of criminological protection of justice, as well as the legislation of Ukraine on criminal liability for criminal offenses against justice, taking  into account experience of Germany and Austria regarding implementation of standards recognized by the international community in this area.Key words: Criminological Protection of Justice; Court Security; Court Security Service; National Police of Ukraine; Criminal Offenses Against Justice.